Using L2 interactional-pragmatic resources in CMC: A case of Japanese orthography and emoji. (March 2022) - Maa, Joy; Taguchi, Naoko
Increasingly prevalent use of technologies such as instant messaging and online chat has transformed our traditional ways of learning and teaching pragmatics. This study presents an example of such transformation by demonstrating how computer-mediated communication (CMC) may be employed as a tool to provide second language (L2) learners opportunities to use interactional resources specific to the context of CMC, namely unique orthography and emoji. For the study, we introduced four university-level learners of Japanese to a language exchange messaging application and recorded their online text-based chat interactions with native Japanese speakers over a period of 12 weeks. We followed up the chat data with weekly stimulated verbal recalls (SVR) to investigate L2 learners' intentions and perceptions surrounding their own and others' use of unique orthography and emoji (48 SVR sessions total; average 30 minutes per session). Coding and thematic analysis of the chat data revealed learners' agentive use of orthography and emoji as resources for communication. In addition, the SVR data revealed a variety of personal and interpersonal reasons behind their use, including learners' concerns over self-presentation, interpersonal relationships, identity, and discourse management. The findings not only demonstrate how CMC can afford learners a unique environment for experimenting with a range of context-appropriate interactional resources to convey pragmatic meaning, but also shed light on the various, sometimes competing, considerations and complex processes underlying learners' pragmatic choices in CMC.